Tabu linguístico: mapeamento das atitudes relacionadas a palavrões e à influência que os fatores sociais, conversacionais, emocionais e de identidade exercem no seu uso cotidiano - Swingler, David Diniz (2016)
There is nothing new about the use of swearwords in human language. In fact, it is believed that swearing is as old as language itself. Studies about swearing, as well as personal experience, show us that this type of language produces a emotional impact that can have both positive and negative effects. Despite its ubiquitous presence in the speech of Brazilians, few linguistic studies have been produced on the subject. Therefore, the present work aims at mapping out the attitudes of college students that frequent Praça da Alegria in regards to swearwords and the influence that social, conversational, emotional, as well as identity factors have in their day-to-day use. According to the existing literature on language attitudes, it is not unusual to encounter gaps or inconsistencies in relation to the language attitudes professed by individuals and what they actually do when they speak (language behavior). Studies show that this contradiction result from the influence of external factors such as context, interlocutor type, place, etc., as well as internal factors such as beliefs, emotions, intentions, etc. Thus, in order to understand the relation between attitudes held about swearwords and swearing in day-to-day social interaction, we have conducted this sociolinguistic research. The present study is of a qualitative nature and is based primarily on an Interactional Sociolinguistic and Ethnography of Communication framework. The corpus used is comprised of data collected from 29 college students at the Universidade Federal da Paraíba (the Federal University of Paraíba) in a recreational area known as Praça da Alegria, using three methods: questionnaires, direct (non-participant) observation and semi-structured interviews. After that, the data was analysed in accordance to the concepts found in Language Attitude theory, as well as Accommodation Theory; and then triangulated in order to guarantee more precise and reliable results. As a result, it was found that: 1) the idea of the meaning of the term swearword, in fact, varied from person to person, nevertheless, there was, in general, a difference between the meaning of the terms swearword and offensive word; 2) the degree of offensiveness of a word is subject to individual opinion; 3) the more offensive a word was considered to be, the less frequently it was said to get used; and 4) social, conversational, emotional and identity factors, in fact, influenced considerably the individuals decision to use or not use this type of language.